Femtosecond‐assisted LASIK flaps resistant to lift secondary to corneal epithelial defects: Case reports and ex vivo studies. Issue 12 (December 2018) - Janbatian, Hrag Yervant; Fadlallah, Ali; Liu, Shaohui; Chu, Tsai; Melki, Samir
Abstract : Purpose : To evaluate why epithelial defects created before femtosecond laser ablation result in laser in situ keratomileusis (LASIK) flaps resistant to lift. Setting : Boston Eye Group, Brookline, Massachusetts, USA. Design : Case reports and ex vivo studies. Methods : To examine the mechanism of resistance to flap lift after epithelial defects, flap creation with a femtosecond laser was performed in 30 fresh porcine eyes. Before ablation, the eyes were assigned to 3 groups. Group 1 was a control group with intact corneal epithelium. In Group 2, a central 2.0 mm corneal epithelial defect was created by marking it with a 2.0 mm trephine. In Group 3, a peripheral 2.0 mm epithelial defect was created similarly. After the femtosecond laser procedure was performed, the flaps were lifted and the resistance to lift was documented. The corneas were further examined using anterior segment optical coherence tomography. Results : In Group 1, no resistance was felt during flap lifts. In Group 2, significant resistance was encountered at the edge of the epithelial defects and the flaps could not be lifted in 7 of 10 eyes. In Group 3, similar significant resistance was encountered in all 10 eyes. Six of 10 flaps could not be lifted. Anterior segment optical coherence tomography from a representative cornea from Group 2 demonstrated a deeper dissection plane in the area where the overlying epithelium was missing. Conclusion : Epithelial defects can interfere with proper LASIK flap creation with the femtosecond laser. This seems to be attributable to a deeper cutting plane under the area of the epithelial defects compared with the surrounding area with intact epithelium.